Security Assessment of LoRaWAN Based IoT Asset Tracking System - Lama, Prabin (My University, 2020)
Asset tracking solutions has a wide range of use including supply chain and logistics, and private property tracking. In the supply chain and logistics industry, asset tracking can increase savings, either it be monetary or time. They can also help with compliance reporting and result in new revenue opportunities for supply chain and logistics operators. The use of LoRaWAN 1.0 protocol in commercial asset tracking system is increasing despite the vulnerabilities in the protocol design pointed out by the security researchers. Security assessment of LoRaWAN based asset tracking system is required to evaluate if the state of the art security mechanism available in the protocol is acceptable enough to be used in the commercial asset tracking systems. A need of proper methodology for the security assessment of the IoT system is long realized in the research community. Also, the need of security requirement analysis process during the system design phase of the Software development life cycle to avoid the security flaws in the final product is much realized. The adapted model of CLASP (Comprehensive, Lightweight Application Security Process), a model proposed by OWASP after years of extensive field work, for effective security requirement analysis is used for the purpose of this study. The security requirement analysis helps bringing important security aspects of any IT system to light, which otherwise are usually overlooked during the development phase. Attack-Defense Tree methodology, an extended version of attack-trees has been around for shorter period and has been proposed recently for security assessment of IoT systems. In this thesis, Attack-Defense Tree methodology is employed for security assessment of the asset tracking system. The graphical illustration of attacks and defense paths are helpful in elucidating security requirements of a system, possible attacks from the adversaries and corresponding security measures. The attributes and their associated values in the attack-defense trees are helpful to assess the likelihood of any attack and its impact. This facilitates in effective risk assessment of any attack against an organization. The selection of attributes and assignment of suitable values to these attributes play important roles in getting the reliable results during the assessment and this can be achieved if careful consideration is made on what domain attributes to focus on while preparing the questions for the quantification during the assessment. This security assessment revealed that the LoRaWAN 1.0.2 have vulnerabilities in the security mechanisms it provides. The use of protocol in the asset tracking systems makes them susceptible to the attacks like eavesdrop, replay-attack, bit-flip attack and ack-spoofing attack and these attacks possess high risks to the organizational operations.
Keywords: LoRaWAN, security requirement analysis, attack-trees, attack-defense trees, ADTools, security assessment.